The History of Compiling Big American Dictionaries in the USA (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Lexicography, the science of dictionary compiling, is closely connected with lexicology, dealing with the same problems the form, meaning, usage and origin of vocabulary units and making use of each other’s achievements.On the one hand, the enormous raw material collected in dictionaries is widely used by linguists in their research. On the other hand, the principles of dictionary making are always based on linguistic fundamentals, and each individual entry is made up in accordance with the current knowledge and findings of scholars in the various lexicological problems always finds reflection in the selection and arrangement of the material. The lexicography studies the compiling just linguistic dictionaries unlike Encyclopedia. But we can’t draw a blunt distinction between the Dictionary and Encyclopedia. But not in vain, there exists such Explanatory-Encyclopedic Dictionaries, which are extremely convenient for our usage.